Strength of soft clay reinforced with 16mm crushed coconut shell column - Farhanis Amirah, Ismail (2018)
Stone column could be used as a ground improvement technique where a portion of soft soil is replaced with granular material such as stone or sand. The benefit of using stone columns in low strength soil has been proved as an efficient method to improve bearing capacity and reduce settlement of soft soils. This study was aimed to investigate the improvement in shear strength of soft clay by embedded with single crushed coconut shell column. This paper was done by determine the height penetration ratio of a single crushed coconut shell column on shear strength characteristics. Unconfined Compression Test (UCT) was conducted for 4 batch kaolin samples including control sample in order to determine the shear strength. The research variable are diameter and height of crushed coconut shell column which under a concept of critical length of column. The increment of shear strength by embedded with crushed coconut shell column are 22.19%, 12.50% and 6.32% with 10.24% area replacement ratio at column penetration ratio of 0.60, 0.80 and 1.00 respectively. From the result obtained, the relationship of the increment of shear strength with the various column penetration show different pattern.